Effects of low energy extracorporeal shockwave therapy on graft incorporation, bone metabolism, pain level and knee functions in individuals with post anterior cruciate ligament reconstruction - Rahim, Marhasiyah (2022)
High energy ESWT has potential to accelerate the healing process of anterior cruciate ligament post reconstruction (ACLR). Evidences regarding the effectiveness of low energy ESWT on clinical outcomes among individuals with post ACLR are scarce. This study aimed to investigate the effects of different frequencies of low energy ESWT on graft incorporation, bone metabolism, pain level and knee functions in individuals with post ACLR. Thirty participants (aged 20-36 years old) being assigned into three groups, i.e. control group (no shockwave therapy sessions), 3 sessions of shockwave therapy (3ESWT group), and 6 sessions of shockwave therapy (6ESWT group) with 10 participants in each group. All participants underwent a single hamstring autograft ACLR and received a similar rehabilitation programme post-operatively. The ESWT was applied once per week for 3 and 6 consecutive weeks. The energy flux density (EFD) used for 6ESWT and 3ESWT groups was 0.18mJ.mm-2 and 0.09mJ.mm-2 respectively (500 shocks, 1.5 bar). The measured parameters included graft incorporation evaluation, bone metabolism markers, pain score and knee function score. The data were collected 5 times, i.e. before ACLR (baseline), 2-, 9-, 12 weeks and 6 months post ACLR. The number of graft with partial incorporation was significantly higher compared to the number of graft without incorporation in 6ESWT group at 6 months post ACLR (p=0.02). However, no significant differences of number of graft with partial incorporation was found among all the groups. There were no significant differences of serum alkaline phosphatase and osteocalcin concentrations between groups, within group and across the five measurements (p>0.05). Serum CTX1 concentrations were also not significantly different within the 3ESWT and 6ESWT groups across the five measurements (p>0.05). Serum calcium concentrations at 2-, 9- and 12 weeks post ACLR were significantly higher compared to its baseline value (p=0.023, p=0.004 and p=0.001 respectively) in comparison of time for all the groups. The pain score was significantly lower at 6 months compared to week 2 post-operatively in comparison of time for all the groups (p=0.039). All intervention and control groups showed significant improvement in Lysholm scores at 6 months post ACLR compared with baseline (p=0.002 for respective group). Six sessions of ESWT exhibited significant effect to accelerate the graft healing by inducing graft incorporation in tibial tunnel, and increased the serum calcium level at 9- and 12 weeks post-operatively. ESWT did not significantly affect bone formation and bone resorption markers post-operatively.